The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1976
DOI: 10.1002/ijc.2910180414
|View full text |Cite
|
Sign up to set email alerts
|

In vitro generation of primary and secondary cytotoxic cell‐mediated immune responses to chemically induced mouse sarcomas

Abstract: Mixtures of lymph node and spleen cells from normal (untreated) BALB/c mice and from BALB/c mice whose syngeneic tumors had been excised 7-28 days previously ("tumor-excised mice"), were sensitized in vitro by cultivation for 9 days with cells from syngeneic, methylcholanthrene-induced sarcomas. The in vitro-sensitized lymphoid cells were tested in a 36-h microcytotoxicity assay for reactivity against target cells carrying the sensitizing tumor antigens, as well as against control target cells lacking these an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…We found that fewer LC taken from multiparous mice and sensitized in vitro were required to kill a significant number of target cells than when LC from virgin mice were similarly sensitized. Our data are therefore in accord with reports from other investigators who have shown that in vitro-sensitized LC can undergo a secondary immune response (MacDonald et al, 1974;Plata et al, 1975;Kall et al, 1976), Lymphoid cells from multiparous mice cultured on 1315 cells or on 12-or 13-day MEF appeared to be more cytotoxic for 1315 and embryo target cells than were LC cultured on embryos of other ages or skin fibroblasts. The cytotoxicity of the LC cultured on skin fibroblasts or on 14-or 15-day MEF might therefore have been present when the LC were placed in culture, rather than acquired during the sensitization process.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that fewer LC taken from multiparous mice and sensitized in vitro were required to kill a significant number of target cells than when LC from virgin mice were similarly sensitized. Our data are therefore in accord with reports from other investigators who have shown that in vitro-sensitized LC can undergo a secondary immune response (MacDonald et al, 1974;Plata et al, 1975;Kall et al, 1976), Lymphoid cells from multiparous mice cultured on 1315 cells or on 12-or 13-day MEF appeared to be more cytotoxic for 1315 and embryo target cells than were LC cultured on embryos of other ages or skin fibroblasts. The cytotoxicity of the LC cultured on skin fibroblasts or on 14-or 15-day MEF might therefore have been present when the LC were placed in culture, rather than acquired during the sensitization process.…”
Section: Discussionsupporting
confidence: 92%
“…Lymphoid cells from mice carrying MCA-induced tumors were also specifically cytotoxic when tested after 3 days in culture with sarcoma cells, but were no longer cytotoxic when tested after 6 days. The cytotoxicity of in vitro-sensitized LC has generally been found to increase when they are incubated for more than 6 days with the sensitizing cells (Mac-Donald et al, 1974;Plata et al, 1975;Glaser et al, 1976;Kall et al, 1976).…”
mentioning
confidence: 99%
“…For the pur poses of this paper, an inhibition assay which demonstrates that WEHI-164, the largest of the cell lines used, does not inhibit non-specifically at blocker/target ratios of 20/1 or less is included (Fig. 6 (Rollinghoff and Wagner, 1973; (Rollinghoff, 1974) and a recent report indicates a similar secondary response to murine sarcomas (Kall et al, 1976 (Prehn, 1975). Tumours that appear rapidly after a high dose of carcinogen are more immunogenic than those that arise a long time after a small dose.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have confirmed the in vitro immunization of lymphocytes by TAA on carcinogen-induced tumours (Warnatz and Scheiffarth, 1974;Small and Trainin, 1975;Kall and Hellstrom, 1975). However, conflicting results have emerged from these in vitro experiments, with claims both that the specificity of the in vitro tumour specific immunity induced is to unique TAA alone (McKhann and Jagarlamoody, 1971;Kall, Hellstrom and Hellstrom, 1976) and that it is to both crossreacting and unique TAA on the same tumour cells (Warnatz and Scheiffarth, 1974). The identity of the effector cytotoxic cells in these in vitro systems was not described.…”
mentioning
confidence: 99%
“…IS were secondarily sensitized to the immunizing neoplasm in vitro by a modification of the technique described by Kall et al (1976). Immune splenocytes were co-cultured with mitomycin-C-treated MCA-1460 at a ratio of 50 splenocytes to each tumor cell for 5 days at 37°C.…”
Section: In Vitro Sensitizationmentioning
confidence: 99%